Perancangan Alat Bantu Penghitung Pentol untuk Mempermudah Proses Pengemasan Berdasarkan Antropometri Pekerja - Firstyawan, Moch. Rizal Gita; Murnawan, Hery (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The "Raja Gresik" meatball factory was established in 2008 and was established in 2018. One of the problems at this factory was that when carrying out the process of packaging meatball in plastic packs, there were packs whose quantity did not match the specifications for the number of meatball of that type. With the existing problems, it is hoped that this research can help the "Raja Gresik" meatball factory to reduce defects in calculating meatball in packs and make workers less tired because the design of the meatball counting tool is in accordance with the anthropomometry of workers. The existence of this tool can reduce losses from an inappropriate number of meatballs in the pack, which will effectively prevent product defects from excess or shortage of meatball. Also, the presence of this tool makes the packaging process time faster from 30 seconds to 23.43 seconds after using this tool. And it can be used for worker anthropometry, namely hand reach length, knee height and standing elbow height.